A case report of massive pulmonary tuberculosis and newly diagnosed systemic lupus erythematosus with complications - Marina Vasilj; Tanja Zovko; Kristina Galic; Marija Goluza Sesar; Natasa Pejanovic Skobic; Katica Pavlovic (Clinical Case Reports)
Key Clinical Message The diagnosis of extensive pulmonary tuberculosis, especially in young people, should take into account the possibility of an associated systemic autoimmune disease. Infections remain an important cause of morbidity and mortalityin systemic lupus erythematosus. This case illustrates the importance of recognizing the association of systemic autoimmune diseases and infections and the need for a multidisciplinary approach.